'A particular Friendship': Bell Barr, Annabella Howard and Sarah Churchill. (4th April 2015) - Thompson, Robert
Abstract : Annabella Dyve (1676–1728), a maid of honour to Princess Anne and later the wife of Sir Robert Howard, is known to have been a pupil of Purcell but has otherwise remained a somewhat shadowy figure. A series of letters to Sarah Churchill, Lady Marlborough, preserved in the Blenheim papers in the British Library, alongside a satirical account of her marriage in Delarivier Manley's The new Atalantis (1709), reveals a range of details about her life and personality, the former source showing that the 'Bell Barr' title given to two works by Purcell refers to her summer retreat in Hertfordshire. In the light of the letters from Howard to Churchill, the literary text of the 'Bell Barr' song I love and I must potentially takes on a private meaning relating to the 'particular friendship' between the two women, while the possible ownership and purpose of the Gresham autograph songbook, its unique source, requires some re-evaluation. The title 'Bell Barr' itself arguably encodes a complex meaning available only to those privy to possibly compromising personal information, and Howard's correspondence suggests that other late songs by Purcell may also share this feature. The difficult relationship between Queen Mary and Princess Anne, with its possible implications for Purcell, is also considered.